Asymmetric synthesis of gem -difluoromethylenated linear triquinanes via cascade gem -difluoroalkyl radical cyclization - Watcharaporn Thaharn (2018)
© 2014 American Chemical Society. An asymmetric synthesis of gem-difluoromethylenated linear triquinanes is described exploiting the synthetic utilities of PhSCF2TMS (5) as a "•CF2- building block. The strategy involves fluoride-catalyzed nucleophilic addition of PhSCF2TMS (5) to chiral ketocyclopentenes 6 to provide silylated adducts 9 or alcohol derivatives 10 and 11. Subsequent cascade radical cyclization of the gem-difluoroalkyl radical generated from silylated adducts 9 or alcohols 10 and 11 afforded gem-difluoromethylenated linear triquinanes 16 as an approximate 1:1 mixture of two diastereomers (16A and 16B). Alternatively, a convenient asymmetric synthesis of gem-difluoromethylenated linear triquinanes 16A can be accomplished by oxidation of 16a (R = H) to provide ketotriquinane 17 followed by a highly stereoselective nucleophilic addition to 17 employing DIBAL, NaBH4, and various Grignard reagents.